Resurrecting phenotypes from ancient DNA sequences: promises and perspectives - Campbell, Kevin L.; Hofreiter, Michael (Prof.) (Canadian Journal of Zoology, 2015)
Anatomical changes in extinct mammalian lineages over evolutionary time, such as the loss of fingers and teeth and the rapid increase in body size that accompanied the late Miocene dispersal of the progenitors of Steller's sea cows (Hydrodamalis gigas (Zimmermann, 1780)) into North Pacific waters and the convergent development of a thick pelage and accompanying reductions in ear and tail surface area of woolly mammoths (Mammuthus primigenius (Blumenbach, 1799)) and woolly rhinoceros (Coelodonta antiquitatis (Blumenbach, 1799)), are prime examples of adaptive evolution underlying the exploitation of new habitats. It is likely, however, that biochemical specializations adopted during these evolutionary transitions were of similar or even greater biological importance. As these "living" processes do not fossilize, direct information regarding the physiological attributes of extinct species has largely remained beyond the range of scientific inquiry. However, the ability to retrieve genomic sequences from ancient DNA samples, combined with ectopic expression systems, now permit the evolutionary origins and structural and functional properties of authentic prehistoric proteins to be examined in great detail. Exponential technical advances in ancient DNA retrieval, enrichment, and sequencing will soon permit targeted generation of complete genomes from hundreds of extinct species across the last one million years that, in combination with emerging in vitro expression, genome engineering, and cell differentiation techniques, promises to herald an exciting new trajectory of evolutionary research at the interface of biochemistry, genomics, palaeontology, and cell biology.